Positive Expectations Feedback Experiments and Number Guessing Games as Models of Financial Markets - Joep Sonnemans; Jan Tuinstra (Tinbergen Institute, 2008)
In repeated number guessing games choices typically converge quickly to the Nash equilibrium. In positive expectations feedback experiments, however, convergence to the equilibrium price tends to be very slow, if it occurs at all. Both types of experimental designs have been suggested as modeling essential aspects of financial markets. In order to isolate the source of the differences in outcomes we present several new treatments in this paper. We conclude that the feedback strength (i.e. the `p-value' in standard number guessing games) is essential for the results. Furthermore, positive expectations feedback experiments may provide good representations of highly speculative markets while standard number guessing games model financial markets with more emphasis on dividend yield and value stocks.
Keywords: C91; G12; 330; number guessing game; beauty contest game; expectations feedback systems; Wiederholte Spiele; Lernprozess; Finanzmarkt; Theorie